Optimalisasi Metode Multiple Intelegence untuk Pengembangan Soft Skill dalam Meningkatkan Kualitas Bonus Demografi Menuju Indonesia Emas 2045 - Sidiq, Ricu; Simamora, Gloria Rosalina; Marpaung, Sri Rahayu; Simatupang, Taty; Tarigan, Gita; Suryani, Ayu (Universitas Pahlawan Tuanku Tambusai, 2024)
The quality of human resources is one of the goals to be achieved in the program to improve soft skills (interpersonal skills). Through quality education, human resources will be achieved that are ready to compete in the work environment. One effort to improve the quality of education is to improve the quality of learning in schools. However, currently Indonesian education is still very far compared to other developing countries. Through the Multiple Intelligence method, it is hoped that the quality of Indonesian education can be improved through improvements in the field of soft skills. The objectives of this research are 1) to determine the influence of interpersonal skills (soft skills) in improving the quality of learning. 2) to find out the implementation of the Multiple Intelligence Method in the learning process in order to improve interpersonal skills (soft skills). The research method was carried out using library research by collecting the most up-to-date information about the research topic and then carrying out in-depth analysis through journals, books and relevant data sources. The information obtained is then arranged in the form of a discussion. The results of the analysis show that the Multiple Intelligences Method (MI can be implemented in the diversity of student intelligence and incorporate it into the learning process. One of the eight intelligences identified by Howard Gardner, focusing on interpersonal intelligence can be a strong foundation for improving student soft skills.